Prostatic-type tissue in the lower female genital tract: a morphologic spectrum, including vaginal tubulosquamous polyp, adenomyomatous hyperplasia of paraurethral Skene glands (female prostate), and ectopic lesion in the vulva - Kazakov, Dmitry V; Stewart, Colin J R; Kacerovská, Denisa; Leake, Robyn; Kreuzberg, Boris; Chudáček, Zdeněk; Hora, Milan; Michal, Michal (The American journal of surgical pathology, 2010)
The investigators report a series of prostatic-type lesions occurring in the lower female genital tract. The cases included a 4.5-cm mass representing hyperplasia of the glandular and stromal tissue of paraurethral Skene gland, a small ectopic prostatic lesion in the vulva, and 4 tubulosquamous vaginal polyps. All lesions were immunopositive for prostate-specific antigen and/or prostatic acid phosphatase. A brief discussion of the earlier published material is included.
Keywords: prostatický specifický antigen; choristom; Female; polypy; prostata; Vaginal Neoplasms; nádory vaginy; Prostate; ženské pohlaví; Choristoma; Urethra; lidé; uretra; hyperplazie; Aged, 80 and over; Prostate-Specific Antigen; tyrosinfosfatasy; Vulvar Diseases; Neoplasms, Complex and Mixed; Polyps; Male; Protein Tyrosine Phosphatases; nádorové biomarkery; Aged; nemoci vulvy; lidé středního věku; nádory komplexní a smíšené; senioři nad 80 let; Biomarkers, Tumor; senioři; mužské pohlaví; Hyperplasia; Middle Aged; Humans